Film Islami: Antara Spiritual dan Komersialisasi di Industri Film Indonesia - Fadilla, Siti; Deni Putra, Muhammad; Rikarno, Riki; Maijar, Andri; Fitri, Dynia (Journal of Religion and Film, 2024)
This study analyzes the representation of Islamic films in Indonesia using a literature review approach, focusing on the interaction between Islamic spiritual values and commercialization in the film industry. With the growing demand for religious content, Islamic films have emerged as a significant genre that both educates and entertains. However, the main challenge is maintaining spiritual integrity amid the pressures of commercialization that dominate the entertainment industry. This research explores how Islamic films depict moral themes, cultural identity, and religious teachings, while also questioning the impact of commercialization on their spiritual messages. The findings show that while there are efforts to convey positive values, some films tend to commodify spirituality to attract audiences. This study emphasizes the importance of awareness and commitment from filmmakers to create works that are not only commercially successful but also authentic in delivering Islamic messages. The results are expected to provide insights for the film industry in developing more meaningful Islamic films that support the spiritual identity of Muslims in Indonesia.